Confluencias de la doctrina jurídica de la Corte Constitucional ecuatoriana 2008-2018: Análisis de redes - Efrén Ernesto Guerrero Salgado; Jefferson Macías Quisaguano (Ius Humani. Jornal do direito, 2019)
The purpose of this study is to demonstrate the patterns of interaction of the doctrine in the jurisprudence of the Ecuadorian Constitutional Court 2008-2018 using the methodology of social network analysis. The doctrine is the set of studies, criticism and analysis of a scientific nature carried out by jurists regarding the Law. In that order of things, the role of “what is read and cited” is vital to understand the epistemological context used in the interpretation of Law, especially scenarios in which constitutional canonical texts can be a value-centered interpretation. In this text, a review was carried out through the methodology of social network analysis, identifying central authors and accelerators of the flow of information, in order to find if there is a common “line of knowledge” used by the Ecuadorian Constitutional Court. It is concluded that a) there is a network of authors in the judgments of the Constitutional Court between the years 2008-2018; b) preponderance of certain main doctrinaires; and, c) a well-connected network of sentences that use doctrine as a tool to proceed, or to improve the quality of the obiter dicta, an element that constitutes a new space for legal analysis and monitoring of the decisions of the High Courts.